Peningkatan Daya Saing Pesantren; Kontribusi Good Corporate Governance dan Informasi Akuntansi Melalui Kinerja Organisasi Pesantren di Kota Jambi - Faturahman, Faturahman; Fikri, Atar Satria; Tanjung, Ferry Saputra (IAIN Kudus, 2024)
Testing the contribution of good corporate governance and accounting information to the competitiveness of Islamic boarding schools through the organizational performance of Islamic boarding schools in Jambi City is the focus of the objective. The associative descriptive type was used in this research. The population and sample are modern Islamic boarding schools in Jambi City using non-probability sampling techniques, namely Islamic boarding schools that have been operating for more than 5 years. Meanwhile, respondents were selected using a purposive technique which included Islamic boarding school administrators, Islamic boarding school students, Islamic boarding school parents, and the general public. The samples obtained were 9 Islamic boarding schools from the 12 currently existing Islamic boarding schools. Linear regression was used to evaluate the data. Based on research findings, good corporate governance and financial information both contribute significantly to the competitiveness of Islamic boarding schools. Meanwhile, good corporate governance really helps the competitiveness of Islamic boarding schools, but accounting information does not. good corporate governance and financial information make a significant contribution to the competitiveness of Islamic boarding schools through organizational performance.